CORPOS NEGROS EXPOSTOS EM UMA PRAÇA DE ALIMENTAÇÃO DE UM SHOPPING - Claudio Mendonça da Silva (Universidade Federal do Maranhão, 2019)
In November 2013, a shopping mall in the state capital of Espírito Santo was the scene of an episode that can be understood as a confirmation action of the existence of institutional prejudice and racism in Brazil. Dozens of young people were treated as citizens without rights by agents of the Military Police, even after the finding of the inexistence of unlawful acts practiced by young people. The "usual" shoppers also recognized as illegitimate the presence of black, poor and suburban residents in a commercial environment located in a prime area of the capital. Documentary and bibliographical research formed the main sources and subsidies for reflections, affirmations and conclusions of this work.